2007
DOI: 10.1109/tbme.2007.897805
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Arterial Stiffness From the Digital Volume Pulse Waveform

Abstract: Cardiovascular disease (CVD) is currently the biggest single cause of mortality in the developed world, hence, the early detection of its onset is vital for effective prevention therapies. Aortic stiffness as measured by aortic pulse wave velocity (PWV) has been shown to be an independent predictor of CVD, however, the measurement of PWV is complex and time consuming. Recent studies have shown that pulse contour characteristics depend on arterial properties such as arterial stiffness. This paper presents a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 15 publications
3
118
2
1
Order By: Relevance
“…Height (meters) was divided by the time between the peaks of the pulse waveform to obtain the ASI in m/s 15. This method has been validated by comparing it with carotid‐femoral PWV in 3 independent studies that concluded both measurements are highly correlated and that ASI is a simple, inexpensive, rapid technique that requires no training and is operator independent 9, 10, 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Height (meters) was divided by the time between the peaks of the pulse waveform to obtain the ASI in m/s 15. This method has been validated by comparing it with carotid‐femoral PWV in 3 independent studies that concluded both measurements are highly correlated and that ASI is a simple, inexpensive, rapid technique that requires no training and is operator independent 9, 10, 16…”
Section: Methodsmentioning
confidence: 99%
“…The shape of the waveform is directly related to the time it takes for the pulse wave to travel through the arterial tree. These tools might be of interest to quickly estimate CVD risk 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the peripheral PPG pulse has been described as becoming ''damped, delayed and diminished'' with increasing severity of vascular disease [1,8]. In order to quantify these morphological changes, various features of the ac PPG pulse have been extracted and analysed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These various analysis techniques have been applied to assess cardiovascular aging and systemic vascular resistance [9,15], endothelial function and the response to vasoactive drugs [17,18], in attempts to assess arterial blood pressure noninvasively [19], and even to assess systemic conditions such as chronic fatigue syndrome [20].…”
Section: Introductionmentioning
confidence: 99%
“…As it is described in [5], the arterial pulse wave is one of the most important signals used on clinical medicine. The analysis of this signal can lead to the diagnosis of several cardiovascular diseases such as arterial stiffness [6,7] and arteriosclerosis [8]. Different optical methods have been previously $ This document is a collaborative effort.…”
Section: Introductionmentioning
confidence: 99%